2009
DOI: 10.1111/j.1467-7687.2009.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of landmarks and boundaries in the development of spatial memory

Abstract: It has been suggested that learning an object's location relative to (1) intramaze landmarks and (2) local boundaries is supported by parallel striatal and hippocampal systems, both of which rely upon input from a third system for orientation. However, little is known about the developmental trajectories of these systems' contributions to spatial learning. The present study tested 5- and 7-year-old children and adults on a water maze-like task in which all three types of cue were available. Participants had to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 48 publications
5
66
1
1
Order By: Relevance
“…The majority of other studies have restricted their investigations of allocentric spatial capacities to children three years and older, and these studies have repeatedly shown that (1) the performance of 3-year-olds on allocentric spatial tasks is inferior to that of older children; (2) children show marked improvement in their allocentric capacities between four and six years of age; and (3) for most of the tasks employed, children's performance becomes adult-like sometime between seven and ten years of age (Bullens et al, 2010;Foreman et al, 1984Foreman et al, , 1990Lehnung et al, 1998;Leplow et al, 2003;Mandolesi, Petrosini, Menghini, Addona, & Vicari, 2009;Nardini, Burgess, Breckenridge, & Atkinson, 2006;Overman et al, 1996;Pentland, Anderson, Dye, & Wood, 2003;Smith et al, 2008). Thus, with the possible exception of Newcombe's study (Newcombe et al, 1998), no study has unequivocally demonstrated that children under three years of age are capable of solving a task which requires the use of an allocentric spatial representation, a fundamental component of episodic memory.…”
Section: Introductionmentioning
confidence: 97%
“…The majority of other studies have restricted their investigations of allocentric spatial capacities to children three years and older, and these studies have repeatedly shown that (1) the performance of 3-year-olds on allocentric spatial tasks is inferior to that of older children; (2) children show marked improvement in their allocentric capacities between four and six years of age; and (3) for most of the tasks employed, children's performance becomes adult-like sometime between seven and ten years of age (Bullens et al, 2010;Foreman et al, 1984Foreman et al, , 1990Lehnung et al, 1998;Leplow et al, 2003;Mandolesi, Petrosini, Menghini, Addona, & Vicari, 2009;Nardini, Burgess, Breckenridge, & Atkinson, 2006;Overman et al, 1996;Pentland, Anderson, Dye, & Wood, 2003;Smith et al, 2008). Thus, with the possible exception of Newcombe's study (Newcombe et al, 1998), no study has unequivocally demonstrated that children under three years of age are capable of solving a task which requires the use of an allocentric spatial representation, a fundamental component of episodic memory.…”
Section: Introductionmentioning
confidence: 97%
“…Also, experiments testing children in a Morris maze paradigm showed that place learning develops up to 7 to 10 years of age (Overman, Pate, Moore, & Peuster, 1996;Lehnung, Leplow, Friege, Herzog, & Ferstl, 1998;Leplow et al, 2003). However, allocentric representations appear to be present in younger children; accurate representations of locations within a testing room have been shown already at 36 months of age (Nardini, Burgess, Breckenridge, & Atkinson, 2006;Newcombe, Huttenlocher, Bullock Drummey, & Wiley, 1998), and children as young as 5 years are able to use a nonegocentric strategy if local landmarks are provided (Bullens et al, 2010;Lehnung et al, 1998). Therefore, converging evidence seems to indicate a gradual acquisition of the ability to use allocentric representations with age.…”
Section: Introductionmentioning
confidence: 99%
“…Estos resultados nos muestran que aparentemente los niños de 6 años, cuando no disponen de la geometría de la habitación exterior, tan sólo utilizan la guía proximal para encontrar la meta. La utilización de la guía no resulta sorprendente, pero sí lo es la incapacidad para emplear tanto la geometría del recinto experimental como la configuración de las claves, lo cual contradice los resultados de gran parte de la literatura (Hermer & Spelke, 1994;Bullens et al, 2010). Según la teoría de los módulos geométricos, la geometría del recinto debería haber sido la primera opción a utilizar por los niños del grupo desorientado, y por otra parte, el empleo de la configuración de las claves antes de los 6 años aparece en numerosos estudios (Overman et al, 1996;Sluzenski et al, 2004).…”
Section: Discussionunclassified